Legal Mechanisms for Business Accountability: A Comparison of Soft and Hard Law in Indonesia - Aspan, Henry; Rosli, Rozaini; Fadlan, Fadlan; Irawati, Irawati (LAW REFORM, 2024)
This research investigates the legal mechanisms for business accountability in the context of Corporate Social Responsibility (CSR) in Indonesia through a comparative study of soft and hard law approaches. The study aims to evaluate the effectiveness of these approaches in promoting business accountability within the Indonesian framework. The research methodology relies on secondary data analysis, including a comprehensive review of existing legal frameworks and regulations related to CSR, as well as an examination of relevant case studies and empirical data. The findings reveal that hard law, characterized by binding regulations and clear sanctions, is more effective in promoting business accountability. However, soft law plays a vital role by offering guidance and incentives for companies to adopt broader social responsibility practices. Cultural factors, the legal environment, and the roles of the government and civil society organizations influence the effectiveness of these approaches. The study highlights the importance of combining hard and soft law approaches in CSR regulation. Recommendations include strengthening monitoring and enforcement by government agencies, offering more substantial incentives, and creating a supportive legal environment. Additionally, companies should understand and respect local culture and commit to anti-corruption efforts. Collaborative efforts among the government, businesses, and civil society are essential for establishing a more sustainable and accountable business environment in Indonesia.